Ceramic-plastic composite, preparation method thereof and electronic device

By setting up glue layers of epoxy resin and other materials between the ceramic and the plastic layer, the brittleness and weight problems of the ceramic materials are solved, the high bonding strength and structural stability of the ceramic plastic composite are achieved, and the user experience of electronic devices is improved .

CN115716356BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110982403.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-25
Publication Date
2025-01-14
Estimated Expiration
2041-08-25

AI Technical Summary

Technical Problem

Due to its high brittleness and high density, ceramic materials are difficult to process into complex structures and have a large weight, which affects the user experience of electronic equipment. It is difficult for the prior art to achieve efficient combination of ceramics and plastics to reduce weight and improve structural stability.

Method used

By setting a glue layer with epoxy resin as the main component between the ceramic layer and the plastic layer, combining phenolic resin and polyurethane, a glue layer with a thickness of 30μm-60μm is formed, the bonding strength between ceramic and plastic is improved and stress is relieved, and gradient heating is used to increase the temperature. Curing and injection molding methods to form a ceramic plastic composite.

Benefits of technology

It realizes high bonding strength and structural stability of ceramic plastic composites, extends service life, reduces the weight of electronic equipment housing, and improves user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115716356B_ABST
    Figure CN115716356B_ABST
Patent Text Reader

Abstract

The present application provides a ceramic-plastic composite, which includes a ceramic layer, a plastic layer, and a glue layer disposed between the ceramic layer and the plastic layer; the glue layer includes epoxy resin; and the thickness of the glue layer is 30 μm-60 μm. The ceramic layer and the plastic layer in the ceramic-plastic composite have high bonding strength, and the glue layer has good corrosion resistance, so that the ceramic-plastic composite has high structural stability and a long service life. The present application also provides a method for preparing the ceramic-plastic composite and an electronic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic composite materials, and in particular to a ceramic-plastic composite body and a preparation method thereof and an electronic device. Background Art

[0002] Ceramics have both the texture of metal and the luster of glass mirrors. When ceramics are made into shells for electronic devices such as mobile phones, the ceramic shells can have the characteristics of wear resistance, skin-friendliness, good impact resistance, and weak electromagnetic shielding. However, due to its high brittleness, ceramics are not conducive to being processed into complex structural parts. In addition, ceramics have a high density, and a heavy ceramic shell will reduce the user experience. Plastics have a low density and are easy to process. Compounding a ceramic layer and a plastic layer is conducive to reducing the weight of the shell and forming a shell with a complex structure. Therefore, it is necessary to provide a ceramic-plastic composite with high structural reliability and a preparation method thereof. Summary of the invention

[0003] To solve the above problems, the present application provides a ceramic-plastic composite, in which the ceramic layer and the plastic layer have high bonding strength, and the glue layer has good corrosion resistance, so that the ceramic-plastic composite has high structural stability and long service life. The present application also provides a method for preparing the ceramic-plastic composite and an electronic device.

[0004] Specifically, the first aspect of the present application provides a ceramic-plastic composite, which includes a ceramic layer, a plastic layer, and a glue layer arranged between the ceramic layer and the plastic layer; the glue layer includes epoxy resin; the thickness of the glue layer is 30μm-60μm.

[0005] In the ceramic-plastic composite of the present application, the epoxy resin in the glue layer has good wettability to both the ceramic layer and the plastic layer, ensuring that the glue layer can fully adhere to the ceramic layer and the plastic layer, thereby improving the bonding strength between the ceramic layer and the plastic layer; when the thickness of the glue layer is 30μm-60μm, the glue layer can not only fully adhere to the ceramic layer and the plastic layer, but also relieve the stress between the ceramic layer and the plastic layer, thereby ensuring that the ceramic-plastic composite has good structural stability.

[0006] Optionally, the glue layer includes one or more of phenolic resin and polyurethane.

[0007] Optionally, a shielding layer is provided between the ceramic layer and the glue layer.

[0008] Optionally, the shielding layer includes an ink layer and / or a glaze layer.

[0009] Optionally, the shielding layer has a thickness of 30 μm-50 μm.

[0010] Optionally, the ink layer includes at least two ink layer sub-layers, and the thickness of the ink layer sub-layers is less than or equal to 30 μm.

[0011] Optionally, the ceramic layer includes one or more of aluminum nitride, silicon nitride, zirconium oxide and aluminum oxide.

[0012] Optionally, the plastic layer includes one or more of polyamide, polycarbonate, polybutylene terephthalate and polyphenylene sulfide. Further, the plastic layer includes polyamide and polybutylene terephthalate.

[0013] Optionally, the plastic layer also includes glass fiber.

[0014] Optionally, the mass percentage of the glass fiber in the plastic layer is 30%-50%.

[0015] Optionally, the thickness of the ceramic layer is 0.2 mm-0.3 mm.

[0016] Optionally, the thickness of the plastic layer is 0.2 mm-0.3 mm.

[0017] Optionally, the bonding strength of the ceramic-plastic composite is greater than or equal to 20 MPa.

[0018] The second aspect of the present application provides a method for preparing a ceramic-plastic composite, comprising:

[0019] Providing a substrate, the substrate comprising a ceramic layer; applying glue on the surface of the substrate and performing a first curing; the glue comprising epoxy resin;

[0020] A plastic layer is formed by injection molding on one side of the substrate coated with glue. The glue is cured for a second time during the injection molding process to form a glue layer, thereby obtaining a ceramic-plastic composite. The thickness of the glue layer is 30 μm-60 μm.

[0021] Optionally, the first curing temperature is 70°C-150°C; the injection molding temperature is 200°C-330°C.

[0022] Optionally, the first curing adopts gradient temperature increase, and the conditions of the gradient temperature increase include: maintaining at 70℃-90℃ for 10min-60min, heating to 100℃-110℃ at a heating rate of 2℃ / min-10℃ / min, maintaining at 100℃-110℃ for 30min-90min, heating to 120℃-150℃ at a heating rate of 2℃ / min-10℃ / min, and maintaining at 120℃-150℃ for 30min-90min.

[0023] Optionally, the glue comprises the following components in percentage by weight: 20%-30% epoxy resin, 1%-5% plasticizer, 1%-5% curing agent and 60%-78% solvent.

[0024] Optionally, the substrate further comprises an ink layer arranged on the surface of the ceramic layer; and coating glue on the surface of the substrate to obtain the substrate coated with glue specifically comprises: coating the glue on the surface of the ink layer.

[0025] Optionally, the method for preparing the ink layer comprises: after coating ink on the surface of the ceramic layer, drying at 70° C.-150° C. for 5 min-100 min to obtain the ink layer.

[0026] Optionally, the method for preparing the ink layer includes: after coating the ink on the surface of the ceramic layer, performing a first drying at 70° C.-90° C., and then performing a second drying at 120° C.-150° C. to obtain the ink layer.

[0027] Optionally, the ink comprises the following components in percentage by weight: 20%-25% polyether polyol; 20%-25% isocyanate; 0.1%-5% colorant; 1%-5% fluorosilicone resin; 0.1%-1% coupling agent; and 39%-58.8% solvent.

[0028] Optionally, the ink is applied more than once.

[0029] The second aspect of the present application provides a method for preparing a ceramic-plastic composite body using glue as an adhesive, and the glue can form a glue layer after curing, and the glue layer can achieve a firm connection between the ceramic layer and the plastic layer, so that the ceramic-plastic composite body has good structural stability.

[0030] The third aspect of the present application provides an electronic device, which includes the ceramic-plastic composite described in the first aspect of the present application or a ceramic-plastic composite prepared by the method for preparing the ceramic-plastic composite described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the structure of a ceramic-plastic composite provided in one embodiment of the present application;

[0032] Figure 2 A flow chart of a method for preparing a ceramic-plastic composite provided in one embodiment of the present application;

[0033] Figure 3 A schematic structural diagram of a ceramic-plastic composite provided in another embodiment of the present application;

[0034] Figure 4A flow chart of a method for preparing a ceramic-plastic composite provided in another embodiment of the present application;

[0035] Figure 5 A schematic diagram of the structure of an electronic device provided in one embodiment of the present application;

[0036] Figure 6 A schematic diagram of a housing structure provided in one embodiment of the present application. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0038] Ceramics have the advantages of high hardness, high mechanical strength, wear resistance, and oxidation resistance. When ceramics are made into the shell of electronic equipment, the ceramic shell has a texture as warm as jade, which can greatly improve the user experience. However, due to the high density of ceramics themselves, as consumer electronic products, especially as products such as mobile phone back panels or watch cases, the heavy weight of the shell will affect the user experience. Plastics have low density and are easy to process. Based on the purpose of lightweight shells and achieving complex structures, it is necessary to develop composite technology for ceramic parts and plastic parts. The present application provides a ceramic-plastic composite, which realizes the connection between the ceramic layer and the plastic layer through a glue layer, and the resulting ceramic-plastic composite has good structural stability and corrosion resistance.

[0039] See also Figure 1 , Figure 1 The ceramic-plastic composite body provided in one embodiment of the present application is a schematic structural diagram. The ceramic-plastic composite body comprises a ceramic layer 10, a glue layer 30 and a plastic layer 20 arranged in sequence, wherein the glue layer 30 is located between the ceramic layer 10 and the plastic layer 20, and the glue layer 30 serves to bond the ceramic layer 10 and the plastic layer 20.

[0040] In an embodiment of the present application, the glue layer includes epoxy resin. The epoxy group in the epoxy resin contains an ether bond, which can promote the bonding between the ceramic layer and the plastic layer. In some embodiments of the present application, the glue layer also includes one or more of phenolic resin and polyurethane. Phenolic resin has good high temperature resistance, which is beneficial to improve the thermal stability of the glue layer and ensure that the glue layer still has strong adhesion after high temperature injection molding. In some embodiments of the present application, the glue layer also includes a plasticizer, which can improve the plasticity of the glue layer, thereby relieving the stress between the ceramic layer and the plastic layer. In an embodiment of the present application, the plasticizer includes one or more of dioctyl phthalate (DOP) and dibutyl phthalate (DBP). In an embodiment of the present application, the thickness of the glue layer is 30μm-60μm. The thickness of the glue layer can be specifically but not limited to 30μm, 40μm, 45μm, 50μm or 60μm. If the thickness of the glue layer is too large, it will cause separation inside the glue layer. If the thickness of the glue layer is too small, the bonding force between the ceramic layer and the plastic layer is low, and the structural stability of the ceramic-plastic composite is poor.

[0041] In an embodiment of the present application, the ceramic layer includes one or more of aluminum nitride, silicon nitride, zirconium oxide and aluminum oxide. In an embodiment of the present application, the thickness of the ceramic layer is 0.2 mm to 0.3 mm. The thickness of the ceramic layer can be, but is not limited to, 0.2 mm, 0.23 mm, 0.25 mm, 0.27 mm or 0.3 mm.

[0042] In an embodiment of the present application, the plastic layer includes one or more of polyamide, polycarbonate, polybutylene terephthalate and polyphenylene sulfide. In some embodiments of the present application, the plastic layer includes polyamide and polybutylene terephthalate. Polyamide and polybutylene terephthalate have good chemical stability, sound insulation and good shock resistance, which are conducive to application in equipment housings. In some embodiments of the present application, the plastic layer also includes glass fiber, and the mass percentage of glass fiber in the plastic layer is 30%-50%. The mass percentage of glass fiber in the plastic layer can be, but not limited to, 30%, 35%, 40%, 45% or 50%. Adding an appropriate amount of glass fiber to the plastic layer can improve the mechanical properties of the plastic layer and ensure that the ceramic-plastic composite has a certain structural strength. In an embodiment of the present application, the thickness of the plastic layer is 0.2mm-0.3mm. The thickness of the plastic layer can be, but not limited to, 0.2mm, 0.23mm, 0.25mm, 0.27mm or 0.3mm.

[0043] The present application also provides a method for preparing the ceramic-plastic composite. Figure 2 , Figure 2 The flow chart of the preparation method of the ceramic-plastic composite provided in one embodiment of the present application. The preparation method of the ceramic-plastic composite comprises:

[0044] Step 100: providing a ceramic layer, coating glue on the surface of the ceramic layer and performing a first curing;

[0045] Step 200: Injection molding is performed on one side of the ceramic layer coated with glue to form a plastic layer. The glue is cured during the injection molding process to form a glue layer, thereby obtaining a ceramic-plastic composite.

[0046] In step 100 of the present application, the ceramic layer can be one or more of aluminum nitride, silicon nitride, zirconium oxide and aluminum oxide. In some embodiments of the present application, the ceramic layer is surface treated to form a rough surface on the side of the ceramic layer close to the plastic layer. The rough surface can improve the adhesion of the glue layer, so that the ceramic-plastic composite has a higher bonding strength. In the embodiments of the present application, the surface treatment includes one or more of sandblasting, chemical etching or laser engraving. In the embodiments of the present application, one or more of a strong alkali and a surfactant are used to clean the ceramic layer so that the ceramic layer has a higher degree of cleanliness.

[0047] In the implementation manner of the present application, the glue includes the following components in percentage by mass: 20%-30% epoxy resin, 1%-5% plasticizer, 1%-5% curing agent and 60%-78% solvent. In some implementation manners of the present application, the glue is prepared using epoxy resin with a grade of E44 or E51. In some implementation manners of the present application, the plasticizer includes one or more of dioctyl phthalate (DOP) and dibutyl phthalate (DBP), the curing agent includes one or more of ethylenediamine and polyetheramine, and the solvent includes one or more of butanone and xylene. The glue of the components of the present application has strong adhesion to ceramics and plastics, and can achieve firm bonding of the ceramic layer and the plastic layer.

[0048] In the embodiment of the present application, when glue is applied to the surface of the ceramic layer, the coating method may be one or more of spraying, dipping and silk-screen printing. In some embodiments of the present application, the glue is applied to the surface of the ceramic layer by a multiple coating method. The coating method of a small amount and multiple times can reduce the bubbles generated during the coating process, and ensure that the formed glue layer has high density and good bonding performance. In some embodiments of the present application, the glue is applied by silk-screen printing, wherein the thickness of the first coating is 5μm-15μm, the thickness of the second coating is 15μm-25μm, and the thickness of the third coating is 5μm-15μm. In the embodiment of the present application, the thickness of the glue applied on the surface of the ceramic layer is 40μm-70μm. The thickness of the glue applied on the surface of the ceramic layer can be specifically but not limited to 40μm, 50μm, 60μm or 70μm.

[0049] Step 100 of the present application may specifically include: providing a ceramic layer; coating glue on the surface of the ceramic layer to obtain a ceramic layer coated with glue; placing the ceramic layer coated with glue at 70°C-150°C for a first curing, and the glue forms an adhesive layer after the first curing; Step 200 of the present application may specifically include: performing injection molding on the surface of the adhesive layer to obtain a plastic layer, and the adhesive layer undergoes a second curing to form a glue layer during injection molding.

[0050] In the implementation manner of the present application, the curing of the glue is divided into a first curing and a second curing, wherein the first curing can remove part of the solvent in the glue and make the glue initially cured to form an adhesive layer, which process can promote the glue to infiltrate the surface of the ceramic layer, so that the adhesive layer is evenly attached to the surface of the ceramic layer. In the implementation manner of the present application, the temperature of the first curing is 70°C-150°C, and the time of the first curing is 5min-100min. The temperature of the first curing can be, but is not limited to, 70°C, 90°C, 100°C, 120°C, 140°C or 150°C. In some embodiments of the present application, the first curing adopts gradient heating, and the conditions of gradient heating include: maintaining at 70℃-90℃ for 10min-60min, heating to 100℃-110℃ at a heating rate of 2℃ / min-10℃ / min, maintaining at 100℃-110℃ for 30min-90min, heating to 120℃-150℃ at a heating rate of 2℃ / min-10℃ / min, and maintaining at 120℃-150℃ for 30min-90min.

[0051] In some embodiments of the present application, the temperature conditions for the first curing are: maintaining at 70°C-90°C for 20min-40min, maintaining at 100°C-110°C for 15min-30min, and maintaining at 120°C-150°C for 20min-40min. The use of a gradient heating method is conducive to increasing the contact surface between the adhesive layer and the ceramic layer, so that the adhesive layer and the ceramic layer have a higher bonding force and surface dryness. During the secondary curing process of the glue, the adhesive layer still has good stability under the injection pressure and is not easily washed away.

[0052] In the embodiment of the present application, the plastic layer is prepared by injection molding, and the preparation method of the plastic layer includes: installing the ceramic layer with the adhesive layer in the injection mold and using the injection plastic material for injection molding and molding, so that the ceramic layer, the glue layer and the plastic layer form an integrated structure. In the embodiment of the present application, the plastic layer can be one or more of polyamide, polycarbonate, polybutylene terephthalate and polyphenylene sulfide. In the embodiment of the present application, the injection molding temperature is 200℃-330℃; the injection molding pressure is 1200kgf / cm 2 -1800kgf / cm 2 , holding pressure is 500kgf / cm 2 -1000kgf / cm2 The holding time is 0.5s-4s. The injection molding temperature may be, but is not limited to, 200°C, 230°C, 250°C, 270°C, 300°C or 330°C, and the injection molding pressure may be, but is not limited to, 1200kgf / cm 2 、1500kgf / cm 2 or 1800kgf / cm 2 The holding pressure may be, but is not limited to, 500 kgf / cm 2 、800kgf / cm 2 or 1000kgf / cm 2 , the holding time can be specifically but not limited to 0.5s, 1s, 2s or 4s. In the embodiment of the present application, the temperature of the injection mold is 100℃-160℃, and the temperature of the plastic raw material during injection molding is 250℃-330℃. Controlling the temperature and pressure during the injection molding process is beneficial to improving the bonding strength between the glue layer and the plastic layer to form a structurally stable ceramic-plastic composite. In the present application, the adhesive layer formed by the first curing of the glue undergoes a second curing during the injection molding process. Specifically, when preparing the plastic layer, the temperature of the plastic injection molding is 200℃-330℃, and the reactive groups on the surface of the adhesive layer are activated at the injection molding temperature, thereby undergoing a cross-linking reaction with the plastic layer, and the adhesive layer and the ceramic layer can also produce further bonding, thereby obtaining a ceramic-plastic composite with higher structural stability.

[0053] The preparation method of the ceramic-plastic composite provided by the present application is simple to operate. In the obtained ceramic-plastic composite, the bonding strength between the glue layer and the ceramic layer or between the glue layer and the plastic layer reaches the level of 5B. In the embodiment of the present application, the bonding strength between the ceramic layer and the plastic layer in the ceramic-plastic composite is greater than or equal to 20Mpa. The bonding strength between the ceramic layer and the plastic layer can be specifically but not limited to 20Mpa, 25Mpa, 30Mpa, 40Mpa, 50Mpa or 60Mpa.

[0054] In the present application, when the ceramic-plastic composite is used as the shell of an electronic device, the surface of the ceramic layer away from the plastic layer is the appearance surface of the shell. For some ceramic layers with lighter colors and thinner thicknesses, their visible light transmittance is higher, resulting in visible structures inside the shell. For example, plastic flow marks will be produced during injection molding of the plastic layer. When the visible light transmittance of the ceramic layer is higher, the internal plastic flow marks can be seen from the outside of the shell, thereby affecting the appearance of the product and reducing the user experience. To solve the above problems, the ceramic-plastic composite includes a ceramic layer, a shielding layer, a glue layer and a plastic layer arranged in sequence. It should be noted that for ceramic layers with dark colors or higher thicknesses, their visible light transmittance is low, and the ceramic layer itself can cover the plastic flow marks, so there is no need to set an additional shielding layer.

[0055] See also Figure 3, Figure 3 A schematic diagram of the structure of a ceramic-plastic composite provided for another embodiment of the present application. Wherein, the ceramic-plastic composite includes a ceramic layer 10, a shielding layer 40, a glue layer 30 and a plastic layer 20 arranged in sequence, and the shielding layer 40 is located between the ceramic layer 10 and the glue layer 30. The shielding layer 40 has a strong covering power and can cover the plastic flow marks to ensure that the shell has a good appearance effect. In the embodiment of the present application, the thickness of the shielding layer is 30μm-50μm. The thickness of the shielding layer can be, but not limited to, 30μm, 35μm, 40μm or 50μm. In the embodiment of the present application, the visible light transmittance of the shielding layer is less than or equal to 2%, and the visible light transmittance of the shielding layer can be, but not limited to, 0.1%, 0.5%, 1% or 2%.

[0056] In the embodiments of the present application, the shielding layer includes an ink layer or a glaze layer. In the present application, the shielding layer is a structure used to shield the interior of the shell. In order not to affect the appearance of the shell, the color of the shielding layer is consistent with the color of the ceramic layer. In some embodiments of the present application, the shielding layer is a glaze layer. The glaze layer has bright colors, which can enhance the visual impact of the ceramic-plastic composite.

[0057] In some embodiments of the present application, an ink layer is used as a shielding layer, wherein the ink layer includes the following raw materials in percentage by weight: polyether polyol 20%-25%; isocyanate 20%-25%; colorant 0.1%-5%; fluorosilicone resin 1%-5%; coupling agent 0.1%-1%; solvent 39%-58.8%. In the present application, the amine group of the polyurethane in the ink layer and the ether bond of the epoxy resin in the glue layer have an intermolecular force, thereby improving the bonding force between the ink layer and the glue layer, and the fluorosilicone resin can improve the high temperature resistance of the ink layer, ensuring that the ink layer does not age and discolor under high temperature conditions. In the embodiments of the present application, the colorant includes an inorganic colorant. In some embodiments of the present application, the colorant includes one or more of titanium white, carbon black, cobalt black, cobalt blue, nickel titanium yellow, copper chrome black, iron red, cobalt green, and iron chrome black.

[0058] In an embodiment of the present application, the thickness of the ink layer is 30μm-50μm. In some embodiments of the present application, the ink layer includes at least two ink layer sublayers, wherein the thickness of the ink layer sublayer is less than or equal to 30μm. The ink layer sublayers can specifically be two layers, three layers or four layers, and the thickness of the ink layer sublayers can specifically be but not limited to 10μm, 15μm, 20μm or 30μm. When the ink layer includes multiple ink layer sublayers, the ink layer as a whole can present a more uniform color and the ink layer has a higher bonding strength with the ceramic layer and the glue layer. In some embodiments of the present application, when the ink layer is used as a shielding layer, the glue layer also includes polyurethane, and the polyurethane has good compatibility with the ink layer, which can enhance the bonding strength between the ink layer and the glue layer.

[0059] In the ceramic-plastic composite of the present application, the ink layer not only has a strong covering power and can cover the plastic flow marks, but also has a high bonding strength with the glue layer and the ceramic layer. In addition, the ink layer has good high temperature resistance. At the injection molding temperature for preparing the plastic layer, the color of the ink layer does not change, thereby ensuring the uniformity of the appearance color of the shell.

[0060] In the ceramic-plastic composite provided by the present application, the bonding strength between the ink layer and the ceramic layer or between the ink layer and the glue layer reaches a level of 5B. In the embodiment of the present application, the bonding strength between the ceramic layer and the plastic layer in the ceramic-plastic composite is greater than or equal to 25Mpa. The bonding strength between the ceramic layer and the plastic layer can be specifically but not limited to 25Mpa, 30Mpa, 40Mpa.

[0061] The present application also provides a method for preparing the ceramic-plastic composite. Figure 4 , Figure 4 This is a flow chart of a method for preparing a ceramic-plastic composite provided by another embodiment of the present application. The method for preparing a ceramic-plastic composite comprises:

[0062] Step 100: providing a ceramic layer; coating ink on the surface of the ceramic layer, and drying at 70° C. to 150° C. for 5 min to 100 min to obtain an ink layer;

[0063] Step 200: coating glue on the surface of the ink layer and performing a first curing;

[0064] Step 300: Injection molding is performed on the side of the ink layer coated with glue to form a plastic layer. The glue is cured during the injection molding process to form a glue layer, thereby obtaining a ceramic-plastic composite.

[0065] In step 100 of the present application, the ceramic layer can be one or more of aluminum nitride, silicon nitride, zirconium oxide and aluminum oxide. In some embodiments of the present application, the ceramic layer is surface treated to form a rough surface on the side of the ceramic layer close to the plastic layer. The rough surface can improve the adhesion of the ink layer and make the ceramic-plastic composite have a higher bonding strength. In the embodiments of the present application, the surface treatment includes one or more of sandblasting, chemical etching or laser etching. In the embodiments of the present application, the ceramic layer is cleaned by plasma cleaning or one or more of a strong alkali and a surfactant, so that the ceramic layer has a higher degree of cleanliness.

[0066] In some embodiments of the present application, the ink includes the following components in percentage by weight: polyether polyol 20%-25%; isocyanate 20%-25%; colorant 0.1%-5%; fluorosilicone resin 1%-5%; coupling agent 0.1%-1%; solvent 39%-58.8%. In the present application, polyether polyol refers to a compound polymerized from a hydroxyl compound and an alkylene oxide. In some embodiments of the present application, the polyether polyol includes one or more of propylene glycol polyether and sorbitol polyether. In the embodiments of the present application, the average molecular weight of the polyether polyol is 7000-15000, and the average molecular weight of the polyether polyol can be, but is not limited to, 7000, 8000, 9000, 10000, 12000 or 15000, 7000. Controlling the average molecular weight of the polyether polyol can ensure that the ink has good pigment dispersibility and strong adhesion. In the embodiment of the present application, the mass percentage of the polyether polyol in the ink may be, but is not limited to, 20%, 23% or 25%.

[0067] In the present application, isocyanate refers to a class of compounds containing isocyanate groups. In some embodiments of the present application, isocyanate includes one or more of toluene diisocyanate and diphenylmethane diisocyanate, and the above isocyanate and polyether polyol can generate polyurethane with strong adhesion. In the embodiments of the present application, the mass percentage of isocyanate in the ink can be, but not limited to, 20%, 22%, 24% or 25%. In the embodiments of the present application, the mass ratio of polyether polyol to isocyanate is 1:(0.8-1.25). The mass ratio of polyether polyol to isocyanate can be, but not limited to, 1:0.8, 1:9, 1:1, 1:1.2 or 1:1.25.

[0068] In the embodiment of the present application, the fluorosilicone resin includes one or more of a polyalkyl fluorosilicone resin and a polyaryl fluorosilicone resin. In the embodiment of the present application, the fluorosilicone resin. In the embodiment of the present application, the mass percentage of the fluorosilicone resin in the ink can be, but not limited to, 1%, 3%, 4% or 5%. In the embodiment of the present application, the coupling agent includes a brand of KH550. In the embodiment of the present application, the mass percentage of the coupling agent in the ink can be, but not limited to, 0.1%, 0.3%, 0.5%, 0.7% or 1%.

[0069] In an embodiment of the present application, the colorant includes an inorganic colorant. In some embodiments of the present application, the colorant includes one or more of titanium white, carbon black, cobalt black, cobalt blue, nickel titanium yellow, copper chrome black, iron red, cobalt green, and iron chrome black. In an embodiment of the present application, the mass percentage of the colorant in the ink can be, but is not limited to, 0.1%, 1%, 2%, 4% or 5%. In an embodiment of the present application, the solvent includes one or more of butanone and xylene. The mass percentage of the solvent in the ink can be, but is not limited to, 39%, 45%, 50%, 55% or 58.8%.

[0070] In the embodiments of the present application, when the ink is applied to the surface of the ceramic layer, the coating method may be one or more of spraying, dipping and silk screen printing. In some embodiments of the present application, the ink is applied to the surface of the ceramic layer by a multiple coating method. The coating method of a small amount and multiple times can reduce the bubbles generated during the coating process, ensure the formation of a smooth and smooth ink layer, and when the multiple coating method is adopted, the ink layer has multiple ink layer sub-layers, and the multiple ink layer sub-layers can ensure that the color of the entire ink layer is relatively uniform, thereby effectively covering the plastic flow marks. In some embodiments of the present application, the ink is applied by a spraying method, wherein the spraying pressure is 100kPa-600kPa. In some embodiments of the present application, the ink is applied by silk screen printing, wherein the thickness of the first coating is 5μm-15μm, the thickness of the second coating is 5μm-15μm, and the thickness of the third coating is 15μm-25μm. In the embodiments of the present application, the thickness of the ink applied on the surface of the ceramic layer is 40μm-60μm. The thickness of the ink coated on the surface of the ceramic layer may be, but is not limited to, 40 μm, 45 μm, 50 μm or 60 μm.

[0071] Step 100 of the present application may specifically include: providing a ceramic body; coating ink on the surface of the ceramic body to obtain a ceramic body coated with ink; placing the ceramic body coated with ink at 70°C-150°C for 5min-100min to obtain an ink layer. In some embodiments of the present application, drying includes first drying and second drying, the temperature of the first drying is 70°C-90°C, the time of the first drying is 5min-50min, the temperature of the second drying is 120°C-150°C, and the time of the second drying is 5min-50min. In some embodiments of the present application, a gradient temperature increase method is used for drying, and the gradient temperature increase conditions include: keeping at 70°C-90°C for 20min-40min, heating to 120°C-150°C at a heating rate of 1°C / min-5°C / min, and keeping at 120°C-150°C for 20min-40min. The use of a gradient heating method is beneficial to increasing the contact surface between the ink layer and the ceramic layer, so that the ink layer and the ceramic layer have a stronger bonding force, and is conducive to forming a flat and smooth ink layer, thereby effectively covering the plastic marks.

[0072] Step 200 of the present application may specifically include: coating glue on the surface of the ink layer, and first curing the glue at 70°C-150°C to form an adhesive layer. In the present application, when glue is coated on the surface of the ink layer and the glue is cured, the polyurethane in the ink layer and the epoxy resin in the glue will bond, thereby achieving a firm bond between the ink layer and the glue layer. After the injection molding is completed, the glue layer and the plastic layer also have a strong bonding force, thereby obtaining a ceramic-plastic composite with a high bonding strength. In the embodiment of the present application, the method for preparing a glue layer on the surface of the ink layer is the same as the method for preparing a glue layer on the surface of the ceramic layer, and will not be repeated here.

[0073] The ceramic-plastic composite of the present application has both good wear resistance of the ceramic layer and good processability of the plastic layer, and the ceramic-plastic composite has uniform color and high aesthetics, which is conducive to market promotion.

[0074] This application also provides an electronic device, see Figure 5 , Figure 5 This is a schematic diagram of the structure of an electronic device provided in an embodiment of the present application. The electronic device 100 includes a display assembly 10 and a housing 20, wherein the housing 20 includes the ceramic-plastic composite of the present application. In the embodiment of the present application, the shape of the housing is not limited to a rectangular parallelepiped, a cylindrical shape or other irregular shapes. Please refer to Figure 6 , Figure 6 A schematic diagram of the housing structure provided in one embodiment of the present application. The housing of the electronic device of the present application is made of a ceramic-plastic composite, which can effectively improve the surface hardness and toughness of the electronic device, and can make the electronic device have a good texture and excellent product competitiveness. In the embodiments of the present application, the electronic device includes a mobile phone, a computer, a watch, a USB flash drive, an electronic cigarette, a wearable device, a digital camera, etc.

[0075] The following is a further description of the implementation methods of the present application with reference to a number of embodiments.

[0076] Example 1

[0077] A method for preparing a ceramic-plastic composite, comprising:

[0078] (1) A white zirconia ceramic layer is taken, the thickness of the zirconia ceramic layer is 0.3 mm, and the visible light transmittance of the zirconia ceramic layer is 20%. The surface of the ceramic layer is cleaned with a sodium hydroxide solution of pH 14 for 30 minutes at room temperature, and then heated and dried to remove moisture from the surface of the ceramic layer.

[0079] (2) Glue with a thickness of 40 μm is screen-printed on the surface of the ceramic layer, wherein the glue includes the following components in percentage by weight: 20% epoxy resin, 1% plasticizer, 1% curing agent and 78% solvent. The epoxy resin is of grade E51, the plasticizer is DOP, the curing agent is ethylenediamine, and the solvent is xylene. The ceramic layer coated with glue is first cured at 100°C for 30 minutes to obtain an adhesive layer. The ceramic layer is placed in a mold and injection molded with polyamide as the raw material at an injection pressure of 1200 kgf / cm 2 , holding pressure 800kgf / cm 2 , the mold temperature is 150° C., the holding time is 4 seconds, and the raw material temperature is 280° C. After the plastic layer is cooled, a ceramic-plastic composite is obtained, in which the thickness of the glue layer is 30 μm and the thickness of the plastic layer is 0.3 mm.

[0080] Example 2

[0081] The difference between Example 2 and Example 1 is that the ceramic layer in Example 2 is a black zirconium oxide ceramic layer, and the first curing of the glue in Example 2 adopts gradient heating, and the gradient heating conditions are: keep at 90°C for 10 minutes, heat to 100°C at a heating rate of 2°C / min, keep at 100°C for 30 minutes, heat to 140°C at a heating rate of 2°C / min, and keep at 140°C for 30 minutes. The thickness of the glue layer in the ceramic-plastic composite of Example 2 is 30 μm.

[0082] Example 3

[0083] The difference between Example 3 and Example 2 is that the coating thickness of the glue in Example 3 is 65 μm, and the thickness of the glue layer in the ceramic-plastic composite of Example 3 is 55 μm.

[0084] Example 4

[0085] The difference between Example 4 and Example 2 is that the ceramic layer in Example 4 is white alumina ceramic, the thickness of the alumina ceramic layer is 0.2 mm, and the visible light transmittance of the alumina ceramic layer is 25%. The material of the plastic layer is polybutylene terephthalate.

[0086] Example 5

[0087] The difference between Example 5 and Example 2 is that the glue in Example 5 includes the following components in percentage by weight: 25% epoxy resin, 2% plasticizer, 1% curing agent and 72% solvent. Among them, the brand of epoxy resin is E51, the plasticizer is DOP, the curing agent is polyetheramine, and the solvent is xylene and butanone.

[0088] Example 6

[0089] (1) A 0.3 mm thick white zirconia ceramic layer with a visible light transmittance of 20% is taken. The surface of the ceramic layer is cleaned with a sodium hydroxide solution of pH 14 for 30 minutes at room temperature, and the surface moisture of the ceramic layer is dried by heating after cleaning.

[0090] (2) Prepare ink according to the following mass percentages of the raw materials: 25% polyethylene glycol; 25% hexamethylene diisocyanate; 5% titanium dioxide; 5% fluorosilicone resin; 1% coupling agent with the brand name KH550; 39% xylene. Apply the ink with a thickness of 35 μm on the surface of the ceramic layer at a spraying pressure of 10 kPa. Dry the ceramic layer coated with the ink at 100° C. for 30 minutes to obtain an ink layer with a thickness of 30 μm.

[0091] (3) Glue with a thickness of 40 μm is screen-printed on the surface of the ink layer. The preparation method of the glue layer and the plastic layer in Example 6 is the same as that in Example 2.

[0092] Example 7

[0093] The difference between Example 7 and Example 6 is that Example 7 uses a screen printing method to apply ink on the surface of the ceramic layer, and the thickness of each application of ink is 5 μm, 10 μm and 20 μm, respectively, and the total thickness of the ink is 35 μm. Keep at 70°C for 30 minutes, heat to 110°C at a heating rate of 2°C / min, keep at 110°C for 30 minutes, heat to 120°C at a heating rate of 2°C / min, and keep at 120°C for 30 minutes. The thickness of the ink layer in the ceramic-plastic composite of Example 7 is 30 μm.

[0094] Example 8

[0095] The difference between Example 8 and Example 7 is that the thickness of each application of ink in Example 8 is 10 μm, 20 μm and 30 μm respectively, and the total thickness of the ink is 70 μm. The thickness of the ink layer in the ceramic-plastic composite of Example 8 is 60 μm.

[0096] Example 9

[0097] The difference between Example 9 and Example 7 is that the ink in Example 9 includes the following raw materials in parts by weight: 25% polypropylene glycol; 25% hexamethylene diisocyanate; 5% titanium dioxide; 5% fluorosilicone resin; 1% coupling agent with brand KH570; and 39% butanone.

[0098] Comparative Example 1

[0099] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, after screen printing glue with a thickness of 40 μm on the surface of the ceramic layer, no first curing is performed, but the ceramic layer is directly placed in a mold for injection molding. The injection molding conditions of Comparative Example 1 are the same as those of Example 1.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Example 1 is that the thickness of the glue coated on the surface of the ceramic layer in Comparative Example 2 is 25 μm. The thickness of the glue layer in the obtained ceramic-plastic composite is 20 μm.

[0102] Comparative Example 3

[0103] The difference between Comparative Example 3 and Example 1 is that the thickness of the glue coated on the surface of the ceramic layer in Comparative Example 2 is 95 μm. The thickness of the glue layer in the obtained ceramic-plastic composite is 80 μm.

[0104] Effect Example

[0105] In order to strongly support the beneficial effects brought by the technical solutions of the embodiments of this application, the following tests are provided:

[0106] 1) Observe the appearance of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3 and measure the thickness of the products, record the apparent effects and thickness of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3, and the thickness of the ceramic-plastic composites is expressed as (ceramic layer thickness) / (glue layer thickness) / (plastic layer thickness) or (ceramic layer thickness) / (ink layer thickness) / (glue layer thickness) / (plastic layer thickness). Please refer to Table 1 for the thickness and apparent effects of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3. The samples after injection molding were processed to obtain products with the following thicknesses.

[0107] Table 1 Thickness and surface effects of ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3

[0108] Experimental Group thickness Surface Effect Example 1 0.3mm / 30μm / 0.3mm Plastic flow marks can be observed Example 2 0.3mm / 30μm / 0.3mm No flow marks, good appearance Example 3 0.3mm / 55μm / 0.3mm No flow marks, good appearance Example 4 0.2mm / 30μm / 0.3mm Plastic flow marks can be observed Example 5 0.3mm / 30μm / 0.3mm No flow marks, good appearance Example 6 0.3mm / 30μm / 30μm / 0.3mm No flow marks, good appearance Example 7 0.3mm / 30μm / 30μm / 0.3mm No flow marks, good appearance Example 8 0.3mm / 60μm / 30μm / 0.3mm No flow marks, good appearance Example 9 0.3mm / 30μm / 30μm / 0.3mm No flow marks, good appearance Comparative Example 1 0.3mm / 30μm / 0.3mm Plastic flow marks can be observed Comparative Example 2 0.3mm / 20μm / 0.3mm Plastic flow marks can be observed Comparative Example 3 0.3mm / 80μm / 0.3mm Plastic flow marks can be observed

[0109] The bonding state of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3 was observed, wherein the bonding effect was in the following order from worst to best: complete separation of ceramic and plastic, partial separation of ceramic and plastic, good bonding, and excellent bonding. The bonding strength of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3 was tested using a universal testing machine. Please refer to Table 2 for the bonding state of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3.

[0110] Table 2 Combination status of ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3

[0111]

[0112]

[0113] 2) The ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3 were subjected to a temperature shock test. The specific test process was as follows: the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3 were placed in a hot and cold shock test box, and the box temperature was adjusted to -40°C for 30 minutes; after 5 minutes, the ceramic-plastic composites were transferred to a hot box and kept at 80°C for 30 minutes; after 5 minutes, the ceramic-plastic composites were transferred to a cold box; the above cycle was repeated 25 times; the product was taken out, and the appearance of the product was observed after cooling and recovering at room temperature for 2 hours. The bonding strength of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3 after the temperature shock test was tested using a universal testing machine. For the results of the temperature shock test, please refer to Table 3, which is a table of the temperature shock test results of the ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3.

[0114] Table 3 Temperature shock test results of ceramic-plastic composites of Examples 1-9 and Comparative Examples 1-3

[0115]

[0116]

[0117] It can be seen from the experimental results in Tables 1 to 3 that the ceramic-plastic composite provided in the embodiments of the present application has higher bonding strength and good high temperature resistance performance and longer service life than the comparative example.

[0118] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A ceramic-plastic composite, characterized in that: The ceramic-plastic composite comprises a ceramic layer, a plastic layer, and a glue layer arranged between the ceramic layer and the plastic layer; the glue layer comprises epoxy resin, a plasticizer and a curing agent; the thickness of the glue layer is 30 μm-60 μm; a shielding layer is arranged between the ceramic layer and the glue layer; the plasticizer comprises one or more of dioctyl phthalate and dibutyl phthalate.

2. The ceramic-plastic composite according to claim 1, characterized in that: The shielding layer includes an ink layer and / or a glaze layer.

3. The ceramic-plastic composite according to claim 2, characterized in that: The shielding layer has a thickness of 30 μm-50 μm.

4. The ceramic-plastic composite according to claim 2 or 3, characterized in that: The ink layer includes at least two ink layer sub-layers, and the thickness of the ink layer sub-layers is less than 30 μm.

5. The ceramic-plastic composite according to claim 1, wherein: The glue layer further comprises one or more of polyurethane and phenolic resin.

6. The ceramic-plastic composite according to claim 1, wherein: The ceramic layer includes one or more of aluminum nitride, silicon nitride, zirconium oxide and aluminum oxide.

7. The ceramic-plastic composite according to claim 1, wherein: The plastic layer includes one or more of polyamide, polycarbonate, polybutylene terephthalate and polyphenylene sulfide.

8. The ceramic-plastic composite according to claim 1, wherein: The thickness of the ceramic layer is 0.2 mm-0.3 mm; the thickness of the plastic layer is 0.2 mm-0.3 mm.

9. The ceramic-plastic composite according to claim 1, wherein: The bonding strength of the ceramic-plastic composite is greater than or equal to 20 MPa.

10. A method for preparing a ceramic-plastic composite according to any one of claims 1 to 9, characterized in that: include: Providing a substrate, the substrate comprising a ceramic layer and a shielding layer arranged on a surface of the ceramic layer; After coating the glue on the surface of the shielding layer, a first curing is performed; The glue comprises epoxy resin, plasticizer and curing agent; A plastic layer is formed by injection molding on one side of the substrate coated with glue. The glue is cured for a second time during the injection molding process to form a glue layer, thereby obtaining a ceramic-plastic composite. The thickness of the glue layer is 30 μm-60 μm.

11. The preparation method according to claim 10, characterized in that: The temperature of the first curing is 70°C-150°C; the temperature of the injection molding is 200°C-330°C.

12. The preparation method according to claim 10 or 11, characterized in that: The first curing adopts gradient heating, and the conditions of the gradient heating include: maintaining at 70℃-90℃ for 10min-60min, heating to 100℃-110℃ at a heating rate of 2℃ / min-10℃ / min, maintaining at 100℃-110℃ for 30min-90min, heating to 120℃-150℃ at a heating rate of 2℃ / min-10℃ / min, and maintaining at 120℃-150℃ for 30min-90min.

13. The preparation method according to claim 10, characterized in that: The glue comprises the following components in percentage by mass: 20%-30% epoxy resin, 1%-5% plasticizer, 1%-5% curing agent, and 60%-78% solvent.

14. The preparation method according to claim 10, characterized in that: The shielding layer comprises an ink layer; and the step of coating the surface of the shielding layer with glue to obtain the substrate coated with glue specifically comprises: coating the glue on the surface of the ink layer.

15. The preparation method according to claim 14, characterized in that: The method for preparing the ink layer comprises: coating the ink on the surface of the ceramic layer, and drying the ceramic layer at 70° C. to 150° C. for 5 min to 100 min to obtain the ink layer.

16. The preparation method according to claim 15, characterized in that: The ink comprises the following components in percentage by mass: 20%-25% of polyether polyol; 20%-25% of isocyanate; 0.1%-5% of colorant; 1%-5% of fluorosilicone resin; 0.1%-1% of coupling agent; and 39%-58.8% of solvent.

17. The preparation method according to claim 15 or 16, characterized in that: The ink is applied more than once.

18. An electronic device, characterized in that: The electronic device comprises the ceramic-plastic composite body as claimed in any one of claims 1 to 9 or the ceramic-plastic composite body obtained by the preparation method as claimed in any one of claims 10 to 17.

Citation Information

Patent Citations

  • Ceramic and plastic complex and preparation method thereof

    CN103895274A

  • Electronic equipment shell and preparation method thereof and electronic equipment

    CN109803508A